The value of administrative behaviors: a comparative study of special education teachers and building administrators in Kansas - Ewy, Casey L. (Kansas State University, 2007)
Finding qualified teachers is a growing concern to school districts nationwide. Special Education is one of those areas that is highly in need. Researchers have suggested the reason for these shortages is not recruitment of special education teachers, but the retention of special education teachers. The research has also shown that lack of effective building administrative support may be a critical factor in a teachers’ decision to stay or leave the field. This study was developed to determine what administrative behavior special education teachers value the most. Additionally, this study sought to find out if there were differences in the administrative behaviors that special education teachers value and what building administrators perceive to be of value. A survey was sent electronically to a random sample of convenience to 200 special education teachers and 200 building administrators in the state of Kansas; 276 surveys were returned. The survey collected data to determine the perceived value of administrative support behaviors by the special education teachers, and any differences of the perceived value of administrative supports by the building administrators. The survey items were categorized into four subgroups of administrative behaviors: emotional, environmental, technical, and instructional. The administrative behaviors of most value to the special education teachers were those that were emotional in nature. Respondents reported that the most valued support actions included providing praise and acknowledging that the teacher makes a difference, supporting the teacher in front of parents, and trusting the teacher’s judgment. Findings also indicated that there were statistically significant differences between what administrative supports special education teachers valued and what building administrators perceive to be of value to special education teachers, with the exception of the technical administrative support actions. These findings suggested that it would benefit school districts positively to implement strategies to evaluate the emotional support provided and desired by their special education teachers as one method to reduce special education teacher attrition. One way of ensuring administrators provide these supports is to hold them accountable, perhaps through policy change in the evaluation process. With recent legislation such as No Child Left Behind, mandating all students receive a quality education form qualified teachers despite the current shortage of special education teachers; administrators must implement strategies to reduce teacher attrition.
Keywords: Special education; Administration; Administrative behaviors; Education, Administration (0514); Education, Special (0529)